Financing for development and small island developing states : a snapshot and ways forward - Hurley, Gail (UN-OHRLLS, 2015)
Provides a snapshot of development financing in small island developing states (SIDS). Aims to inform and reinvigorate international policy debates around how SIDS can finance and meet the world's new sustainable development agenda, the SDGs. Makes a series of recommendations.